2007
DOI: 10.1016/j.physletb.2006.10.070
|View full text |Cite
|
Sign up to set email alerts
|

Another step towards a no-lose theorem for NMSSM Higgs discovery at the LHC

Abstract: We show how the LHC potential to detect a rather light CP-even Higgs boson of the NMSSM, H 1 or H 2 , decaying into CP-odd Higgs states, A 1 A 1 , can be improved if Higgs-strahlung off W bosons and (more marginally) off top-antitop pairs are employed alongside vector boson fusion as production modes. Our results should help extracting at least one Higgs boson signal over the NMSSM parameter space.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 61 publications
1
40
0
Order By: Relevance
“…As for present accelerator machines, chiefly the Tevatron at FNAL and the Large Hadron Collider (LHC) at CERN, quite some work has been dedicated to probing the NMSSM Higgs sector over recent years. Primarily, there have been attempts to extend the so-called 'No-lose theorem' of the MSSM -stating that at least one MSSM Higgs boson should be observed via the usual SM-like production and decay channels at the LHC throughout the entire MSSM parameter space [8] -to the case of the NMSSM [6,9,10,12,13]. From this perspective, it was realised that at least one NMSSM Higgs boson should remain observable at the LHC over the NMSSM parameter space that does not allow any Higgs-to-Higgs decay.…”
Section: Introductionmentioning
confidence: 99%
“…As for present accelerator machines, chiefly the Tevatron at FNAL and the Large Hadron Collider (LHC) at CERN, quite some work has been dedicated to probing the NMSSM Higgs sector over recent years. Primarily, there have been attempts to extend the so-called 'No-lose theorem' of the MSSM -stating that at least one MSSM Higgs boson should be observed via the usual SM-like production and decay channels at the LHC throughout the entire MSSM parameter space [8] -to the case of the NMSSM [6,9,10,12,13]. From this perspective, it was realised that at least one NMSSM Higgs boson should remain observable at the LHC over the NMSSM parameter space that does not allow any Higgs-to-Higgs decay.…”
Section: Introductionmentioning
confidence: 99%
“…Their work also studied the 2b2τ mode and found that it's prospects were not as promising. For older work on the 4b and 2b 2τ modes, see (79,80,81,82,83,84).…”
Section: Higgs Decays To Scalarsmentioning
confidence: 99%
“…In recent years much effort has been focused on establishing a "nolose theorem" at the LHC in which detection of at least one Higgs boson in the NMSSM is guaranteed. However, the potential importance of the decay h 1 → A 1 A 1 [21], [28] has prevented such a theorem being established [19], [29], [30], [31], [32]. Moreover, it has been shown that a large branching ratio for h 1 → A 1 A 1 would weaken the LEP bounds for a SM like h 1 in the NMSSM [2].…”
Section: H ± In the Nmssmmentioning
confidence: 99%